Multicultural Values in the New Paradigm of Al Islam and Kemuhammadiyahan as an Effort to Prevent Radiacialism in Muhammadiyah Universities - Irfani, Muhammad; Ali Mustofa, Triono (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The rise of an understanding of radicalism, especially in the university environment, indicates that conditions in that environment are not good - fine, the biggest factor in the increasingly widespread understanding of radicalism is because someone is wrong when he understands religion. Muhammadiyah, which is an Islamic organization that is concerned with education, has a step to ensure that students stay on the